2004
DOI: 10.1016/j.chembiol.2004.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Intravenous Transgene Expression in Mouse Lung Using Cyclic-Head Cationic Lipids

Abstract: Herein, we report enhanced intravenous mouse lung transfection using novel cyclic-head-group analogs of usually open-head cationic transfection lipids. Design and synthesis of the new cyclic-head lipid N,N-di-n-tetradecyl-3,4-dihydroxy-pyrrolidinium chloride (lipid 1) and its higher alkyl-chain analogs (lipids 2-4) and relative in vitro and in vivo gene transfer efficacies of cyclic-head lipids 1-4 to their corresponding open-head analogs [lipid 5, namely N,N-di-n-tetradecyl-N,N-(2-hydroxyethyl)ammonium chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 37 publications
1
62
0
Order By: Relevance
“…In another recent study, inspired by the previously reported high gene transfer activities of cationic lipids with one or two 2-hydroxyethyl functionalities in the polar head-group regions, 36,39,[41][42][43] we designed and synthesized a novel cationic lipid containing three 2-hydroxyethyl functionalities in the head-group region and evaluated its in vitro gene transfer efficacies in multiple cultured cells. 75 These findings demonstrate that the transfection efficacies of fatty acid-laden lipoplexes are worth evaluating particularly when traditional cationic liposomes prepared with either cholesterol or DOPE co-lipids fail to transfect cultured cells.…”
Section: F Influence Of Co-lipidsmentioning
confidence: 99%
See 2 more Smart Citations
“…In another recent study, inspired by the previously reported high gene transfer activities of cationic lipids with one or two 2-hydroxyethyl functionalities in the polar head-group regions, 36,39,[41][42][43] we designed and synthesized a novel cationic lipid containing three 2-hydroxyethyl functionalities in the head-group region and evaluated its in vitro gene transfer efficacies in multiple cultured cells. 75 These findings demonstrate that the transfection efficacies of fatty acid-laden lipoplexes are worth evaluating particularly when traditional cationic liposomes prepared with either cholesterol or DOPE co-lipids fail to transfect cultured cells.…”
Section: F Influence Of Co-lipidsmentioning
confidence: 99%
“…Interestingly, as mentioned below under the section on ''pre-clinical successes,'' the in vivo lung transfection efficacies of the cyclic-head lipids were found to be remarkably superior to their open-head analogs. 43 Recently, we have observed that the in vitro gene delivery efficiencies of cationic lipids with hydroxyalkyl head-groups get adversely affected by increased covalent distances between the hydroxyl functionality and the cationic centers. 72 Our recent findings have demonstrated that even truly minor structural modification, such as inclusion of an additional one methylene group in the head-group region (lipid 8, Fig.…”
Section: B Influence Of Head-group Nature and Head-group Chargesmentioning
confidence: 99%
See 1 more Smart Citation
“…To extend the current study toward targeting breast cancer in tumor-bearing mice we chose to include DODEAC as the base cationic lipid, which has a proven in vivo biodistribution profile (30). The idea of including polyethylene glycol in cationic lipid-mediated gene transfection in vivo is to suppress the usual nonspecific lung affinity by increasing the longevity of the liposome in the body.…”
Section: Discussionmentioning
confidence: 99%
“…However, with a PEG spacer between the lipid and HP, there is efficient ligand-mediated targeting by the liposome. Additionally, the PEG moiety also provides improved stability and an increased circulation halflife of the liposome in vivo (29,30,21,22).…”
Section: Discussionmentioning
confidence: 99%